2009
DOI: 10.2320/jinstmet.73.103
|View full text |Cite
|
Sign up to set email alerts
|

Friction Stir Weldability of High Tensile Strength Mg Alloy to Al Alloy

Abstract: Friction stir weldability of a fine grained high tensile strength AZ31 magnesium alloy to an Al Mg alloy A5083 was evaluated by changing joining parameters, such as tool rotating speed, welding speed and insertion position of probe. A square butt dissimilar joint without any defect was obtained at the condition of welding speed 100 mm/min, tool rotating speed 500 rpm and offset 0 mm, by using a tool with shoulder diameter of 15 mm, pin diameter of 5 mm and pin length of 3.9 mm. Higher or lower welding speeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Besides Al, Al 3 Mg 2 is present on the fracture surface on the AA5083 side. Several previous works 24,[28][29][30][31][32] on the mechanical properties of dissimilar welds have suggested that the weld strength is affected by the thickness of the IMC layer formed at the interface. Yamamoto et al 24 observed a marked drop of the tensile strength when the IMC layer was thicker than 1?8 mm in the butt friction stir weld of AA5083 to AZ31.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides Al, Al 3 Mg 2 is present on the fracture surface on the AA5083 side. Several previous works 24,[28][29][30][31][32] on the mechanical properties of dissimilar welds have suggested that the weld strength is affected by the thickness of the IMC layer formed at the interface. Yamamoto et al 24 observed a marked drop of the tensile strength when the IMC layer was thicker than 1?8 mm in the butt friction stir weld of AA5083 to AZ31.…”
Section: Resultsmentioning
confidence: 99%
“…To build such vehicles, reliable processes are needed to join dissimilar materials. For a number of combinations of dissimilar metals, such as Al alloy/ steel 17,18 and Al alloy/Mg alloy, [19][20][21][22][23][24][25][26][27][28] a well known issue has been the formation of brittle intermetallic compounds (IMCs) in the welds. Since the presence of such IMCs usually reduces ductility of the welds drastically, traditional fusion welding processes, which usually produce huge IMCs in the fusion zone, are not acceptable in most cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major issue when welding dissimilar Mg∕Al alloys is the formation of Al 3 Mg 2 and Mg 17 Al 12 intermetallic compounds (IMCs) in a large quantity, which have a detrimental effect on joint strength [4,5] . Other issues are their different physical properties (e.g., thermal expansion, conductivity) and the limited mutual solid solubility of Mg and Al [6][7][8] . Previous studies have been carried out with the goal of understanding and controlling the growth of Mg-Al IMCs [9][10][11][12][13][14] .…”
mentioning
confidence: 99%
“…Recently, the degree to which FSW can join dissimilar metals had been investigated in the combinations of Mg/Al [2][3][4][5] , Al/Ti 6) and Mg/Ti [7][8][9] . Among them, Mg/Ti dissimilar joining by FSW was investigated between Mg-Al-Zn alloy and commercial pure titanium.…”
Section: Introductionmentioning
confidence: 99%